Metformin [Working Title] 2020
DOI: 10.5772/intechopen.91263
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of Metformin on Ocular Complications in Patients with Type 2 Diabetes

Abstract: Diabetes mellitus (DM) as a chronic condition is a growing global problem. Its numerous complications, including ocular diseases, affect patients' quality and length of life. Metformin is an effective, safe, and inexpensive first-line pharmacotherapy for type 2 diabetes (T2D). The current evidence indicates metformin's multiple sites of action and multiple molecular mechanisms leading to its beneficial impact on metabolism, inflammation, oxidative stress, aging, as well as to its cardiovascular, neurological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…T2D management encompasses lifestyle education programs and glycemic regulation by the use of oral antidiabetic agents. These increase insulin secretion from the pancreatic β cells, reduce insulin resistance as well as the postprandial glycemia [ 20 ]. Metformin (MTF) is a biguanide, recommended as first-line therapy of T2D in non-pregnant adults by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2D management encompasses lifestyle education programs and glycemic regulation by the use of oral antidiabetic agents. These increase insulin secretion from the pancreatic β cells, reduce insulin resistance as well as the postprandial glycemia [ 20 ]. Metformin (MTF) is a biguanide, recommended as first-line therapy of T2D in non-pregnant adults by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MTF displays an inhibitory effect on the complex I of the ETC [ 25 ]. It was shown that MTF plays a protective role for both photoreceptors and RPE [ 20 , 26 ]. MTF can also be utilized in combination with sulfonylureas such as glibenclamide (GLB), also known as glyburide in the US.…”
Section: Introductionmentioning
confidence: 99%
“…This protective association of DM against OHT is more important as the study cohort had 70% of patients with diabetes, and the main indication for intravitreal injection was DME, and still, the analysis found its association to be protective. There are ample reports on both the protective and risk association of DM with glaucoma [22][23][24][25]. HC also acts as a protective factor for SI-OHT, but there are no published reports for its protective association with SI-OHT, making our findings more authentic.…”
Section: Discussionmentioning
confidence: 52%
“…Metformin is associated with few side effects, both in the sense of frequency and severity, and has been observed to be appropriate for a number of conditions, both solely and as an adjuvant, facilitating treatment. It can add substantially to treatment combinations to prevent irreversible and severe stages and enable a faster recovery in critical disorders, including tuberculosis and ocular complications ( Maleškić et al, 2017 ; Han et al, 2018 ; Xu S et al, 2018 ; Kusturica et al, 2020 ). However, there is a need to evaluate metformin in clinical trials before including it in the regime of conventional therapy plans for such critical disorders.…”
Section: Future Perspectivesmentioning
confidence: 99%